Snowball Effect of Interest Rate as a Control Instrument On Inflation Framework Targetingin Indonesia - Sriyono Sriyono (Journal of Economics, Business, & Accountancy Ventura, 2016)
Afterthe monetary crisisthe government changes its monetary policy strategyby using a new paradigm that Inflation Targeting framework. This new paradigm has been confirmed in Law No.23 of 1999and UUNo3 of 2004as the basis forthe application of Inflation Targeting Framework inIndonesia The purpose ofthis studywas to determine whether interest rates only impact on inflation or even cause greater impact on other monetary variables. It is very important to knowthe impact,by knowing the impact it can avoid unwanted conditions Data of research is collected since 1970 to 2013, hypothesis testing is used econometric models. The main advantages of econometric models for being able to handle the mutual dependence (interdependence). Beside that econometric model is an invaluable tool for understanding the workings of the economic system and  so to test and evaluate policy alternatives andhypothesis testing using multiple regression. The result of this study showed that this study indicate the interest rate turns out not only as an instrument of control of Inflation Targeting Framework but cause a snowball effecton other monetary variables that further strengthen themechanismonInflationTargetingFramework